Methods, Approaches and Data Sources for Estimating Stocks of Irregular Migrants - Jandl, Michael (International migration, 2011)
This paper presents a comprehensive review of available methods for sizing irregular migrant populations as a particular group in the study of hidden populations. Based on the existing body of literature on the subject, a generic classification scheme is developed that divides existing estimation procedures into subcategories like “approaches”, “methods” and “estimation techniques”. For each of these categories, basic principles, methodical strengths and weaknesses, as well as practical problems, are identified and discussed with the use of existing examples. Special emphasis is placed on data requirements, data shortcomings and possible estimation biases. In addition, based on the empirical classification and quality assessment of country‐specific estimates developed in the CLANDESTINO research project, the potential and requirements for replicating best practice models in other countries are explored. Finally, a number of conclusions on the appropriate design of estimation projects are offered.